2011
DOI: 10.1016/j.arr.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

B cells and immunosenescence: A focus on IgG+IgD−CD27− (DN) B cells in aged humans

Abstract: a b s t r a c tImmunosenescence contributes to the decreased ability of the elderly to control infectious diseases, which is also reflected in their generally poor response to new antigens and vaccination. It is known that the T cell branch of the immune system is impaired in the elderly mainly due to expansion of memory/effector cells that renders the immune system less able to respond to new antigens. B lymphocytes are also impaired in the elderly in terms of their response to new antigens. In this paper we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 159 publications
(194 reference statements)
7
87
1
1
Order By: Relevance
“…So our results might be due to different circumstances. As previously published (Bulati et al 2011), and as shown here, IgG ? IgD -CD27 -DN B cells show a low frequency of somatic mutation, and this supports the theory that these cells might emerge independently from T cell help, or from CD40-CD154 interaction.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…So our results might be due to different circumstances. As previously published (Bulati et al 2011), and as shown here, IgG ? IgD -CD27 -DN B cells show a low frequency of somatic mutation, and this supports the theory that these cells might emerge independently from T cell help, or from CD40-CD154 interaction.…”
Section: Discussionsupporting
confidence: 91%
“…This leads us to the hypothesis that there is a large population of DN cells that are unrelated to classical memory B cells. The increase of the double negative memory B cells in the elderly (Colonna-Romano et al 2009;Bulati et al 2011), together with the reduced rate of mutation shown here, might be due to the disconnected generation of these cells from germinal centers, as it has been demonstrated that ageing negatively affects the germinal center formation in secondary lymphoid tissues (William et al 2002;Frasca et al 2005).From this and our previous papers (Colonna-Romano et al 2009 we can conclude that DN B lymphocytes are exhausted cells. In fact they are not activated by anti-CD40/IL4, or by CpG/PMA/Ionomycin and behave differently as CMV-specific effector-memory CD8 lymphocytes.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Although the total numbers of mature B cells decrease with age (reviewed in Frasca et al 2011), conflicting reports on the ratio of naïve and memory cells exists (Kolar et al 2006;Caraux et al 2010;Bulati et al 2011;Frasca et al 2011). Furthermore, a decrease in classswitched B cells and decrease in affinity antibodies has been observed in the elderly (Frasca et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This topic is still a somewhat controversial finding, as previously reviewed by us . Moreover, double-negative (DN) B cells (IgD − CD27 − ) are significantly increased in the elderly (Colonna-Romano et al 2009;Bulati et al 2011), as well as under certain pathological conditions, such as systemic lupus erythematosus (SLE) (Anolik et al 2004;Wei et al 2007), chronic HIV infection (Cagigi et al 2009), and in healthy subjects challenged with respiratory syncytial virus (Sanz et al 2008).…”
Section: Cd24mentioning
confidence: 99%